2004
DOI: 10.1590/s0034-72992004000300014
|View full text |Cite
|
Sign up to set email alerts
|

Emissões otoacústicas por produtos de distorção em crianças de 2 a 7 anos

Abstract: Palavras-chave: emissões otoacústicas, perda auditiva, triagem auditiva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
1
6
3
1
Order By: Relevance
“…We did not find significant differences in relation to gender, and this is different from the research carried out by Dell'Aringa et al 12 which found a higher rate of DPOAE failures in males.…”
Section: Frazzacontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not find significant differences in relation to gender, and this is different from the research carried out by Dell'Aringa et al 12 which found a higher rate of DPOAE failures in males.…”
Section: Frazzacontrasting
confidence: 99%
“…Dell'Aringa et al 12 , studied 93 school and preschool aged children within the age range of 2 and 7 ears of age, through distortion product otoacoustic emissions and found a rate of 5.7% of hearing alterations, which is below the result found in the present investigation when compared to the frequency of altered otoacoustic emissions. They concluded that, otoacoustic emissions proved useful to perform screening in this age range.…”
Section: Frazzacontrasting
confidence: 79%
See 1 more Smart Citation
“…Hypoacousis prevalence determined among the Kaiowá and Guarani children was lower than the one noted by Vallejo et al 21 of 9.7% in non-indigenous children and similar to what was found by Dell'Aringá et al 22 In the attempt to approximate results of this study with others accomplished with non-indigenous children it is important to be aware of methodology interpretation issues specially concerning the fact that health conditions of nonindigenous children are different from the Kaiowá and Guarani children with very high morbidity and mortality rates caused by respiratory diseases, diarrheas and malnutrition which certainly impact conductive hearing.…”
Section: Hypoacousis Prevalence In Indigenous Childrensupporting
confidence: 85%
“…Authors who performed the DPOAE in 105 children found that 5.37% presented alterations 28 . DPOAE was also performed in 846 children from another study, in which 96% of the subjects passed the hearing screening 29 , similar to the data found in the present study.…”
mentioning
confidence: 99%